The antiviral protein viperin inhibits HCV replication via interaction with NS5A - Helbig, Karla J. (2011)
The interferon-stimulated gene viperin has been shown to have antiviral activity against hepatitis C virus (HCV) in the context of the HCV replicon, although the molecular mechanisms responsible are not well understood. Here we demonstrate that viperin plays an integral part in the ability of interferon to limit replication of cell culture derived HCV (JFH-1) that accurately reflects the complete viral life cycle. Using confocal microscopy and Fluorescence Resonance Energy Transfer (FRET) analysis we demonstrate that viperin localizes and interacts with HCV NS5A at the lipid droplet interface. In addition viperin also associates with NS5A and the pro-viral cellular factor, VAP-A at the HCV replication complex. The ability of viperin to limit HCV replication was dependent on residues within the C-terminus as well as an N-terminal amphipathic helix. Removal of the amphipathic helix redirected viperin from the cytosolic face of the ER and the lipid droplet to a homogenous cytoplasmic distribution, coinciding with a loss of antiviral effect. C-terminal viperin mutants still localized to the lipid droplet interface and replication complexes but did not interact with NS5A proteins as determined by FRET analysis. In conclusion we propose that viperin interacts with NS5A and the host factor VAP-A to limit HCV replication at the replication complex. This highlights the complexity of host control of viral replication by interferon stimulated gene expression.